Motherhood in India glorification without empowerment? - Krishnaraj, Maithreyi (London Routledge, 2010)
Contributed articles presented earlier at a residential workshop commenting on motherhood and feminist thoughts in India.
Includes bibliographical references and index.
Keywords: Motherhood -- India -- Congresses; Feminism -- India -- Congresses